How pre-start up assessment helps software companies in Agile transition - Gandomani, Taghi Javdani; Zulzalil, Hazura; Javanmardi, Ali; Abdul Ghani, Abdul Azim; Md Sultan, Abu Bakar; Nafchi, Mina Ziaei (Publications International, 2013)
While prevalence of Agile methodologies is increasing these years, companies should be aware of challenges that may they face during changing their development approach. Agile methods focus on people and this makes transition process more difficult than people expect. Companies should be ready for Agile transition, and performing a pre-start up assessment may help them to be best prepared for the change. Conducting a Grounded Theory study involving 33 Agile experts from 13 different countries showed that pre-start up assessment can help companies in various aspects including defining business goals, addressing training needs, team set up, pilot project selection and method or practice selection. In pre-start up assessment organization and team members should be evaluated to discover their abilities, requirements and restrictions. This process helps companies to get ready for moving to Agile.